Awareness of Testicular Cancer and Testicular Self-Examination among Men in Bahrain - Alaradi, Maryam; Almuqamam, Ayman (Asian Pacific Journal of Cancer Care, 2020)
Introduction: Although testicular cancer (TC) is a rare tumor accounting for 1% of malignancies in men, it is the most common cancer found in adolescents and young men between 15 to 35 years old. Routine screening for TC is not recommended. Therefore, testicular self-examination (TSE) is an important tool for the early detection of TC. If detected early, TC has a high survival rate. Increasing awareness of TC and TSE is crucial for early detection, diagnosis, and treatment. We aimed to assess the level of awareness of TC and TSE among men in Bahrain. Materials and methods: A descriptive cross-sectional design was used to recruit a convenience sample of 243 men from public places using a questionnaire. Descriptive statistics and Chi-square test were conducted. Results: The results showed that 43% were Bahraini, 53% were aware that men can get TC, 82% perceived themselves as having a low risk for developing TC, 15% knew signs of TC, 20% heard about TSE, and 5.8% reported performing TSE. A significant association between knowledge of early signs and symptoms of TC and nationality (p = .006), perception of the importance of performing TSE regularly and nationality (p = .003), and between age (p = .013), level of education (p = .015) and the willingness to perform TSE if the participant was educated about TSE. Conclusion: Awareness about TC and TSE is poor among men in Bahrain. Policymakers in the Ministry of Education and Ministry of Health may consider integrating TC and TSE education in the curriculum and the healthcare provided to adolescents and young men across the kingdom.